2013
DOI: 10.1159/000354246
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Associated Plasma Protein-A as a Marker of Culprit Lesion Instability in Unstable Angina Patients: An Intravascular Ultrasound Study

Abstract: Background: We evaluated the relationship between pregnancy-associated plasma protein-A (PAPP-A) and coronary plaque instability as assessed by intravascular ultrasound (IVUS). Methods: We performed greyscale IVUS analysis in culprit lesions of 93 patients with unstable angina (UA) and 72 with stable angina (SA). A sandwich enzyme-linked immunosorbent assay technique was used to assay circulating PAPP-A. Results: Patients with UA had higher PAPP-A levels than those with SA 10.8 mIU/l [interquartile range (IQR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…24 In in vitro studies, PAPP-A has been demonstrated to be a specific activator of insulin-like growth factor-I (IGF-I), which stimulates migration and proliferation of smooth muscle cells, production and accumulation of foam cells, and degradation of extracellular matrix. 2527 Our previous grayscale-IVUS study demonstrated that higher circulating PAPP-A levels were associated with echo-attenuated plaques, 28 a grayscale IVUS marker of plaque instability. 6,29 Grayscale IVUS, however, is limited to tissue characterization, especially for necrotic core-rich plaques.…”
Section: Discussionmentioning
confidence: 99%
“…24 In in vitro studies, PAPP-A has been demonstrated to be a specific activator of insulin-like growth factor-I (IGF-I), which stimulates migration and proliferation of smooth muscle cells, production and accumulation of foam cells, and degradation of extracellular matrix. 2527 Our previous grayscale-IVUS study demonstrated that higher circulating PAPP-A levels were associated with echo-attenuated plaques, 28 a grayscale IVUS marker of plaque instability. 6,29 Grayscale IVUS, however, is limited to tissue characterization, especially for necrotic core-rich plaques.…”
Section: Discussionmentioning
confidence: 99%